Social capital and immigrant wealth inequality: Visa sponsorship and the role of ties, education, and race/ethnicity. (December 2015) - Painter, Matthew A.
Highlights: Visa sponsorship is associated with wealth inequality. This relationship differs by the strength of an immigrants' tie to their network. This relationship differs by immigrants' education. Race/ethnicity stratifies the wealth of immigrants with employment sponsorship. Abstract: This paper examines how immigrants' social capital affects their wealth holdings in the United States. I conceptualize visa sponsorship as a form of social capital and focus on three important factors – strength of ties, educational attainment, and race/ethnicity – that shape the relationship between immigrants' social capital and wealth. I use the New Immigrant Survey and find that the relationship between visa sponsorship and wealth differs both by the strength of an immigrants' tie to their network and their education. Notably, race/ethnicity only consistently stratifies the wealth of immigrants with employment sponsorship. Taken together, these results provide unique insight into immigrants' economic integration in the United States and point to immigrants' social capital as an important mechanism for wealth inequality.